GOOD GOVERNANCE DALAM PEMBANGUNAN JALAN DI DESA SIALANG INDAH KECAMATAN PANGKALAN KURAS KABUPATEN PELALAWAN TAHUN 2022 - Ananda, Muhammad Rizky; Asrida, Wan (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2024)
The transformation of the political system from centralization to decentralization in Indonesia, as stipulated in Law No. 32 of 2004 and its revisions, transfers authority from the central government to the regions. The success of this system is highly dependent on collaboration between the government, the private sector, and the community in implementing the principles of Good Governance, which include community participation, transparency, accountability, and effectiveness in managing development. This study aims to analyze the application of the principles of Good Governance in a road construction project in Sialang Indah Village and identify factors that influence the success of the project. These findings are expected to provide recommendations for improvements in the implementation of village development, so that it is more in accordance with the needs of the community and the principles of Good Governance. This study uses a qualitative approach with descriptive methods, and data collection using interview and documentation techniques. This study uses the theory put forward by Sedarmayanti, namely Good Governance as the implementation of good and responsible governance, as well as efficient and effective, by maintaining the synergy of constructive interactions between the domains of the state, private sector, and community. The results show that the principles of community participation, transparency, and accountability have been implemented well, but the effectiveness of implementation needs to be improved. Challenges such as delays, poor coordination, and budget management issues, as well as internal and external constraints, affected the final results. Additional actions are needed to improve effectiveness and efficiency to maximize benefits to the community. Keywords: Good Governance, Village Development, and Village Government.